Concentration Camp or Colonization? Brief Reflections on Human Rights Today - de Jesus Oliveira, Marcos (2024)
This essay aims to present two important paradigms that inform part of the contemporary debate on human rights, namely, the concentration camp paradigm represented by thinkers such as Hannah Arendt, Giorgio Agamben, Judith Butler and, to a lesser extent, Michel Foucault, and the colonization paradigm represented by Aimé Césaire, Frantz Fanon, Walter Mignolo and Achille Mbembe. To achieve the objective, we will begin with a brief presentation of the hegemonic version of the human rights discourse with its main assumptions. The thought of the political scientist Norberto Bobbio is taken as an example of this predominant perspective. Despite the differences between the thinkers, we present some of the main ideas of the concentration camp paradigm and then confront them with the reflections made by thinkers who dared to consider colonization not as a “mere” historical event, but as a theoretical landmark, reorganizing the way we interpret the relationship between modernity and right. Finally, the need for an interepistemic dialogue between the two paradigms is suggested as a way to expand the grammars of human dignity in a world increasingly marked by the disrespect for human rights.